Noninvasive detection of audiovisual superadditivity in rat brain by miniaturized SERF magnetometer - Kexun Tang; Guanzhong Lu; Peixin Zhang; Hao Wang; Zixuan Wang; Jia Yao; Yi Ruan; Qiang Lin (PLoS ONE, 2026)
The neural mechanisms of multisensory integration, particularly the superadditive response where combined sensory inputs elicit neural activity exceeding the sum of unimodal responses, remain a central frontier in perceptual and cognitive neuroscience. Utilizing a high sensitivity spin exchange relaxation free atomic magnetometer (SERF AM), we noninvasively record event related magnetic fields (ERMFs) in anesthetized rats during audiovisual (AV) stimulation, demonstrating the first application of SERF technology in rodent multisensory research. Comparisons across auditory-only, visual-only, and AV conditions revealed superadditive enhancement of the M300 component, with amplitudes surpassing the linear sum of unimodal responses. This effect is modulated by sound frequencies and inter-stimulus intervals (ISIs), suggesting dual modulation: frequency dependent consistency and ISI dependent emergence enhancement. AV induced M300 delays may reflect increased processing time under multisensory stimulation. The observed pattern of early suppression and later enhancement is consistent with condition dependent modulation across different stages of audiovisual processing. The approach advances cross species mechanistic understanding and provides a scalable platform for future translational research in neurodevelopmental conditions.